Molecular dynamics simulation on the adhesion mechanism at polymer‐mold interface of microinjection molding. Issue 13 (20th October 2020) - Yang, Jin; Zhai, Zhanyu; Liu, Jiezhen; Weng, Can
Abstract: In the demolding process of microinjection molding, the defects of microstructures are often caused by the strong adhesion between polymer and mold. In order to study the adhesion mechanism, the molecular dynamics (MD) method was proposed to simulate the adsorption of cycloolefin copolymer (COC) molecules on mold surfaces. The evolution snapshots of COC molecular chains of three interfacial models were obtained to directly demonstrate the adhesive strength of interfaces. Meanwhile, the work of adhesion, the relative concentration, the potential energy, and the radial distribution function (RDF) were calculated to explain the interaction mechanism of polymer‐mold interfaces. The simulation results showed that the COC‐Ni interface had the largest work of adhesion and the lowest potential energy, compared with other two interfaces. The van der Waals (VDW) energy, which mainly derived from the interaction between H atoms in COC and the mold material was the only nonbond interaction energy at the COC‐Ni and COC‐Si interfaces, while the electrostatic energy existed in COC‐Al2 O3 interface. In order to reduce the adhesion between polymer and mold, fluorine (F) element could be doped into the Ni mold. Abstract :